Gasto público e desenvolvimento: uma análise do gasto público municipal maranhense na função educação para os anos de 2007 e 2015 - MATOS, Roberto Santos (2017)
The purpose of this essay is to evaluate the quality of municipal public spending in education for the years 2007 and 2015. For this purpose, it is based on an exposition about the constitutional principles and other aspects inherent to the public administration that make it possible to conceptualize and qualify spending public. The study then, presents the forms of classification of expenditure in the budget item and its relevance as an instrument of social control. The determinants of public spending are discussed in the light of the main theories and strategies of development, as well as the influence that these theories have in the formulation of the legislations of the country that govern public finances nowadays. It is also review the educational policy trajectory and the financing of education in Brazil from the Federal Constitution of 1988, both in terms of public policy management and legislation, and in terms of educational results obtained by the country in the period after re-democratization. The educational profile of Maranhão is revealed through specific indicators of the area. The model used is the Public Spending Quality Index (PSQI), created by Bertê, Brunet and Borges. The data used come from the National Treasury Secretariat - NTS, School Census and Prova Brasil, both linked to the National Institute of Studies and Educational Research Anísio Teixeira - INEP. Data processing is performed using some statistics tools, such as the score standardized by the normal cumulative distribution function method, the calculation of the coefficients of determination (R²) and the "quartile" measure of position. The evaluation of municipal public spending in Maranhão is carried out in three ways, the first being compared to other municipalities in the country, the second in relation to the aggregate of municipalities per federative unit, and the third, in turn, among the municipalities of Maranhão. It was observed, from the behavior of the data for the years considered, that the growth of the expenditure per student does not necessarily translate into the increase of the quality of the expenditure in education, revealing the inefficacy of a significant set of municipalities in Maranhão.